ФЕМИНИЗМ БА ЭМЭГТЭЙЧҮҮДИЙН ЭРХИЙН ТӨЛӨӨ ТЭМЦЭЛ - Ё.Довчин; Б.Одгэрэл (Politology, 2023)
In the beginning of XIX century, women have no right to participate in politics. And they have passed long way to obtain equal right to vote in politics. Since XV century “Ideology women equality in social life” has come up. But we considering in this context only since XIX century. In this context all about feminist wave in political right.